IDNLearn.com: Your reliable source for finding expert answers. Discover prompt and accurate responses from our experts, ensuring you get the information you need quickly.
Sagot :
To analyze the statements about the graph of the inequalities [tex]\( y \leq 3x + 1 \)[/tex] and [tex]\( y \geq -x + 2 \)[/tex], let's go through each statement step-by-step.
1. The slope of one boundary line is 2:
- The first inequality is [tex]\( y \leq 3x + 1 \)[/tex], which has a boundary line [tex]\( y = 3x + 1 \)[/tex] with a slope of 3.
- The second inequality is [tex]\( y \geq -x + 2 \)[/tex], which has a boundary line [tex]\( y = -x + 2 \)[/tex] with a slope of -1.
- Since neither slope is 2, this statement is false.
2. Both boundary lines are solid:
- The inequality [tex]\( y \leq 3x + 1 \)[/tex] uses [tex]\( \leq \)[/tex], which means the boundary line [tex]\( y = 3x + 1 \)[/tex] is solid.
- The inequality [tex]\( y \geq -x + 2 \)[/tex] uses [tex]\( \geq \)[/tex], which means the boundary line [tex]\( y = -x + 2 \)[/tex] is solid.
- Therefore, this statement is true.
3. A solution to the system is [tex]\((1, 3)\)[/tex]:
- Substituting [tex]\( x = 1 \)[/tex] and [tex]\( y = 3 \)[/tex] into the first inequality [tex]\( y \leq 3x + 1 \)[/tex]:
[tex]\[ 3 \leq 3 \cdot 1 + 1 \implies 3 \leq 4 \quad \text{(true)} \][/tex]
- Substituting [tex]\( x = 1 \)[/tex] and [tex]\( y = 3 \)[/tex] into the second inequality [tex]\( y \geq -x + 2 \)[/tex]:
[tex]\[ 3 \geq -1 + 2 \implies 3 \geq 1 \quad \text{(true)} \][/tex]
- Since [tex]\((1, 3)\)[/tex] satisfies both inequalities, this statement is true.
4. Both inequalities are shaded below the boundary lines:
- The inequality [tex]\( y \leq 3x + 1 \)[/tex] is shaded below the line [tex]\( y = 3x + 1 \)[/tex].
- The inequality [tex]\( y \geq -x + 2 \)[/tex] is shaded above the line [tex]\( y = -x + 2 \)[/tex].
- Since the second inequality is not shaded below its boundary line, this statement is false.
5. The boundary lines intersect:
- To find the intersection point of the lines [tex]\( y = 3x + 1 \)[/tex] and [tex]\( y = -x + 2 \)[/tex], set the equations equal to each other:
[tex]\[ 3x + 1 = -x + 2 \][/tex]
Solving for [tex]\( x \)[/tex]:
[tex]\[ 3x + x = 2 - 1 \implies 4x = 1 \implies x = \frac{1}{4} \][/tex]
Substituting [tex]\( x = \frac{1}{4} \)[/tex] into [tex]\( y = 3x + 1 \)[/tex]:
[tex]\[ y = 3 \cdot \frac{1}{4} + 1 = \frac{3}{4} + 1 = 1.75 \][/tex]
- Thus, the intersection point is [tex]\( \left( 0.25, 1.75 \right) \)[/tex], confirming the lines intersect. Therefore, this statement is true.
Summary:
- The slope of one boundary line is 2: False
- Both boundary lines are solid: True
- A solution to the system is [tex]\((1, 3)\)[/tex]: True
- Both inequalities are shaded below the boundary lines: False
- The boundary lines intersect: True
1. The slope of one boundary line is 2:
- The first inequality is [tex]\( y \leq 3x + 1 \)[/tex], which has a boundary line [tex]\( y = 3x + 1 \)[/tex] with a slope of 3.
- The second inequality is [tex]\( y \geq -x + 2 \)[/tex], which has a boundary line [tex]\( y = -x + 2 \)[/tex] with a slope of -1.
- Since neither slope is 2, this statement is false.
2. Both boundary lines are solid:
- The inequality [tex]\( y \leq 3x + 1 \)[/tex] uses [tex]\( \leq \)[/tex], which means the boundary line [tex]\( y = 3x + 1 \)[/tex] is solid.
- The inequality [tex]\( y \geq -x + 2 \)[/tex] uses [tex]\( \geq \)[/tex], which means the boundary line [tex]\( y = -x + 2 \)[/tex] is solid.
- Therefore, this statement is true.
3. A solution to the system is [tex]\((1, 3)\)[/tex]:
- Substituting [tex]\( x = 1 \)[/tex] and [tex]\( y = 3 \)[/tex] into the first inequality [tex]\( y \leq 3x + 1 \)[/tex]:
[tex]\[ 3 \leq 3 \cdot 1 + 1 \implies 3 \leq 4 \quad \text{(true)} \][/tex]
- Substituting [tex]\( x = 1 \)[/tex] and [tex]\( y = 3 \)[/tex] into the second inequality [tex]\( y \geq -x + 2 \)[/tex]:
[tex]\[ 3 \geq -1 + 2 \implies 3 \geq 1 \quad \text{(true)} \][/tex]
- Since [tex]\((1, 3)\)[/tex] satisfies both inequalities, this statement is true.
4. Both inequalities are shaded below the boundary lines:
- The inequality [tex]\( y \leq 3x + 1 \)[/tex] is shaded below the line [tex]\( y = 3x + 1 \)[/tex].
- The inequality [tex]\( y \geq -x + 2 \)[/tex] is shaded above the line [tex]\( y = -x + 2 \)[/tex].
- Since the second inequality is not shaded below its boundary line, this statement is false.
5. The boundary lines intersect:
- To find the intersection point of the lines [tex]\( y = 3x + 1 \)[/tex] and [tex]\( y = -x + 2 \)[/tex], set the equations equal to each other:
[tex]\[ 3x + 1 = -x + 2 \][/tex]
Solving for [tex]\( x \)[/tex]:
[tex]\[ 3x + x = 2 - 1 \implies 4x = 1 \implies x = \frac{1}{4} \][/tex]
Substituting [tex]\( x = \frac{1}{4} \)[/tex] into [tex]\( y = 3x + 1 \)[/tex]:
[tex]\[ y = 3 \cdot \frac{1}{4} + 1 = \frac{3}{4} + 1 = 1.75 \][/tex]
- Thus, the intersection point is [tex]\( \left( 0.25, 1.75 \right) \)[/tex], confirming the lines intersect. Therefore, this statement is true.
Summary:
- The slope of one boundary line is 2: False
- Both boundary lines are solid: True
- A solution to the system is [tex]\((1, 3)\)[/tex]: True
- Both inequalities are shaded below the boundary lines: False
- The boundary lines intersect: True
Thank you for joining our conversation. Don't hesitate to return anytime to find answers to your questions. Let's continue sharing knowledge and experiences! IDNLearn.com is your source for precise answers. Thank you for visiting, and we look forward to helping you again soon.